Drawn‐on‐Skin Sensors from Fully Biocompatible Inks toward High‐Quality Electrophysiology (Small 36/2022). Issue 36 (8th September 2022) - Patel, Shubham; Ershad, Faheem; Lee, Jimmy; Chacon‐Alberty, Lourdes; Wang, Yifan; Morales‐Garza, Marco A.; Haces‐Garcia, Arturo; Jang, Seonmin; Gonzalez, Lei; Contreras, Luis; Agarwal, Aman; Rao, Zhoulyu; et al.
Abstract : Biocompatible Conductive Inks In article number 2107099, Cunjiang Yu and co‐workers report the recent development of a conductive ink that is fully biocompatible at the cell, tissue, and organ levels. It also allows for conformal interfacing with human skin for high‐fidelity electrophysiological measurements. This cover illustrates the conformal contact of the ink film with skin.